Pembuatan Aplikasi Auto Generate Content Pada PT Digital Artisan Solusindo - Stefanus Eko Prasetyo; Haeruddin; Elvis (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2025)
PT Digital Artisan Solusindo faces challenges in efficiently producing relevant, SEO-friendly digital content due to time and resource constraints. This community service project aimed to design and build a prototype application for auto-generating content to address this issue. The application integrates two key technologies: Google Trends, used to identify real-time popular topics, and the Gemini AI Large Language Model (LLM), which automatically generates articles based on these trends. The development process followed the Software Development Life Cycle (SDLC) methodology, encompassing requirements analysis through interviews, system design using flowcharts and use case diagrams, implementation with PHP and the Laravel framework featuring the Laravel Horizon queue manager, and functional testing. The result is a functional prototype deployed on Amazon Web Services (AWS) cloud infrastructure. It can automatically fetch trends, process them into prompts, generate content via Gemini AI, and store it in a database. This prototype provides a successful solution for automating content creation at PT Digital Artisan Solusindo, saving time and resources, and holds the potential to be developed into a new, innovative service product